Evaluasi Manajemen Aset Teknologi Informasi menggunakan Framework Cobit 5 Proses EDM04 dan BAI09 : Studi pada PT. Perkebunan Nusantara XI - Dio Wisnu Hamjono; Suprapto Suprapto; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Ministrial regulation number PER-02/MBU/02/2018 on State-owned Enterprise's IT Governance Principles states that state-owned enterprise (SOE) needs to implement IT governance to ensure good corporate governance. PT. Perkebunan Nusantara which is one of an SOE has fulfilled said needs with their creation of IT master plan. The IT master plan states that to ensure IT could support business strategies and goals there is a need for an IT capability audit. This research is an IT governance evaluation using COBIT 5 framework that aims to discover PT. Perkebunan Nusantara XI's (PTPN XI) IT capabilities on IT asset and service management. This research uses EDM04 (ensure resource optimization) process and BAI09 (manage IT assets) for their relation on optimizing cost and performance of IT asset. Evaluation found PTPN XI has capability level 2 on EDM04 process with 1,5 gap value, and capability level 1 on BAI09 process with 2,5 gap value. Recommendation for EDM04 is to documentate IT service capabilities evaluation, and for BAI09 to documentate the IT service capabilities on business requirements, IT assets cost optimization, and license audit.